Milling quality and grain translucency of irrigated rice as affected by nitrogen fertilizer - Silva, Paulo Sérgio Lima e; Brandão, Sylvio Starling (Pesquisa Agropecuaria Brasileira, 2014)
Length, width, translucency and milling quality are very important traits in determining the rice value for marketing. Aiming to evaluate the influence of nitrogen fertilization rates (0,45 and 90 kg of N/ha) on these traits, a trial was carried out with the rice cultivars IAC-435, De Abril, CICA 4, IR-634, IR-661 and IR-665. Nitrogen did not significantly influence width nor length of the grains of the genotypes tested nor proportion of full grains of IAC-435, CICA 4, IR-634 and IR-661. Nitrogen had a positive effect on the grain translucency of IAC-435, De Abril and IR-665, and on the head yield of IR-665, but negatively affected this character in the De Abril cultivar.